Nuansa Harmoni di Alam Kebhinekaan: Praktik Toleransi di Situs-situs Religi Indonesia - Ramadhan, Tri; Sulasiah, Sulasiah; Bagaskara, Faishal; Chair, Abdul (Universitas Islam Negeri Raden Intan Lampung, 2022)
The link between pilgrimage tourism, pluralism, and tolerance on religious communities is often a hot topic that can be common concern because it can be a parameter of society harmony. One of the interesting issues to discuss is how the relationship between religious communities around religious sites. This article will focus on the practices of inter-religious tolerance in five representative place of religious sites, namely Banten Lama, Telukbetung Lampung, Sam Po Kong Semarang, Maria Ambarawa Cave, and Bukit Kasih Toar Lumimu'ut. The five places are considered representative in presenting space of harmony between religious communities because in one location there are more than one religious site. The method used in this article is qualitative method with observation, interview, and literature study. The results showed that tolerance was still maintained at all of these sites and could be used as a role model of tolerance. By maintaining tolerance, it is hoped that it can help our government and society in strengthening harmony and overcoming the problems of ethnicity, religion, race and intergroup (SARA) which have recently surfaced.